1999
DOI: 10.1046/j.1365-2370.1999.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of HLA‐DR2 haplotypes in Caucasoid Americans, African Americans, Chinese Americans, Native Americans and Xiamen Chinese

Abstract: HLA-DR, -DQ specificities were determined by PCR amplification with SSOP in 4560 individuals: Caucasoid Americans (CA), African Americans (AA), Chinese Americans (ChA), Native Americans (NA) and Xiamen Chinese (XC). DR2 subtypes were compared amongst the five ethnic populations. The DRB1*1501-DRB5*0101 haplotype was found to be the most frequent in all populations except African Americans, in which DRB1*1503-DRB5*0101 was the predominant haplotype, accounting for 65% of DR2 subtypes. In contrast to Caucasoid A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Leaving that epicenter, the frequencies decreased concentrically (Figure 2; Solberg et al, 2008). The HLA-DRB1*15:03 commonality in black Americans (26.3%; Lee et al, 1999), Colombians (18%, 15%, and 13%, respectively, for Providencia, Cauca, and Choco groups; Trachtenberg et al, 1996), and Jamaicans (10.2%; Heward et al, 2002) suggests that HLA-DRB1*15:03 could be an ethnic marker of African origin. Our analyses showed that HLA-DRB1*15:03 allele was significantly more frequent among our black-skinned EBA patients from sub-Saharan countries than the control population, comprised of individuals from sub-Saharan countries where this incidence had been determined (Middleton et al, 2003;Solberg et al, 2008): Central African Republic (Aka Pygmies), Mali, Ethiopia, Zimbabwe, and Senegal, with the exception of Cameroon.…”
Section: Discussionmentioning
confidence: 95%
“…Leaving that epicenter, the frequencies decreased concentrically (Figure 2; Solberg et al, 2008). The HLA-DRB1*15:03 commonality in black Americans (26.3%; Lee et al, 1999), Colombians (18%, 15%, and 13%, respectively, for Providencia, Cauca, and Choco groups; Trachtenberg et al, 1996), and Jamaicans (10.2%; Heward et al, 2002) suggests that HLA-DRB1*15:03 could be an ethnic marker of African origin. Our analyses showed that HLA-DRB1*15:03 allele was significantly more frequent among our black-skinned EBA patients from sub-Saharan countries than the control population, comprised of individuals from sub-Saharan countries where this incidence had been determined (Middleton et al, 2003;Solberg et al, 2008): Central African Republic (Aka Pygmies), Mali, Ethiopia, Zimbabwe, and Senegal, with the exception of Cameroon.…”
Section: Discussionmentioning
confidence: 95%
“…HLA phenotypes of all subjects were determined by sequence-specific oligonucleotide probe hybridization (SSOPH) (Lee et al, 1996(Lee et al, , 1999Wu et al, 2004).…”
Section: Determination Of Hla Phenotypesmentioning
confidence: 99%
“…To study the relationship between HLA phenotypes and HCV viral load, we have determined the phenotypes of HLA-A, -B, and -DRB1 for all anti-HCV positive subjects by sequence-specific oligonucleotide probe hybridization (SSOPH) (Lee et al, 1996(Lee et al, , 1999Wu et al, 2004). Due to small sample size for subjects with HBsAg-positivity, we subsequently restricted further analyses to HBsAg-negative subjects only.…”
Section: Association Of Hla Phenotypes and Subtypes With Hcv Viral Loadmentioning
confidence: 99%
“…This DRB1 allele is mainly associated with DRB5*010101 and DQB1*0602, but it has been described either without the DRB5 gene or with any other DQB1 allele [27]. EXON 1 10 20 30 40 50 60 70 80 90 100 DRB1*110101 ATGGTGTGTCTGAGGCTCCCTGGAGGCTCCTGCATGGCAGTTCTGACAGTGACACTGATGGTGCTGAGCTCCCCACTGGCTTTGGCTGGGGACACCAGAC DRB1*111101 ************************************************************************************** The complete coding region of DRB1*1503 was sequenced from two Spanish Caucasian individuals, both demonstrating the predicted DRB1*1503-DRB5*010101-DQA1*010201-DQB1*0602 haplotype (Table 3).…”
Section: Drb5-associated Alleles: Drb1*1503 and Drb1*1504mentioning
confidence: 99%